Pelteobagrus fulvidraco culturing feed and preparation method thereof - MA LI; ZHANG ZHIYONG (2016)
The invention relates to the field of aquatic feed processing, and discloses pelteobagrus fulvidraco culturing feed and a preparation method thereof. The feed provided by the invention is prepared from Peru fish meal, bean pulp, flour, soya-bean oil, monocalcium phosphate, zeolite powder, saltwater fish compound premix, feed grade calcium propionate, vitamin C and an antioxidant. The pelteobagrus fulvidraco culturing feed provided by the invention adopts multiple proper components, fish oil commonly used in a traditional feed formula is removed, meanwhile, a cold spraying technology of cooling the feed first and then spraying grease is adopted for preparation, the prepared feed can reduce the feed coefficients and increase the specific growth rate and relative weight gain rate of pelteobagrus fulvidraco.